Henry Clay Derrick papers - Derrick, Henry Clay, 1832-1915.; Derrick, Clarence
Diaries (1875-1878) recording Derrick's service with other former Confederate and Union soldiers in the Egyptian army (Jaysh) under the Khedive as an engineer conducting surveys and preparing maps. Includes a description of a military expedition into Abyssinia (1875). The papers also include transcripts and synopses of portions of the diaries and Derrick's letters to his wife, Martha Frances Cosby Derrick, and other family members, edited and annotated by Clarence Derrick; inventory of books in his library; and photocopies of clippings and other related papers.
Army officer and civil engineer, of Halifax, Va.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Derrick family; Derrick, Martha Frances Cosby -- Correspondence; Confederate States of America. -- Army -- Officers; Egypt. -- Jaysh; Military maps; Egypt -- Maps; Egypt -- History -- Ismail, 1863-1879.; Ethiopia -- History -- 1490-1889.; Civil engineers; Soldiers